Physical and mechanical properties of artocarpus integer peel paper / Fairuzdzah Ahmad Lothfy … [et al.] - Ahmad Lothfy, Fairuzdzah; Shafie, Amran; Mohd Fouzi, Nor Hidayah; Zaraji, Siti Norhajatul Aina; Ahmad, Nur Ashikin (Universiti Teknologi MARA Cawangan Pahang, 2020)
There are some environmental problems that are faced when producing papers from trees such as deforestation, air pollution, greenhouse gas emissions and disposal of animal habitats. Jackfruit waste such as the peel could be used as a new raw material for producing papers and at the same time, it could reduce problems with waste disposal due to the peel being solid waste. The objectives of this research are to fabricate the Artocarpus Integer peel (AIP) paper and study its physical and mechanical properties. The basic weight of AIP paper is 80.76-85.30 g/m2 and the bulk is 1.18-1.27 cm3/g. The fabricated AIP paper shows that it has good folding, tearing index, tensile strength, strain, and tensile energy absorption. The porosity size of AIP paper is 31.58 μm. Thus, utilizing AIP as an alternative raw material could increase the economic value, help to reduce the cost of disposal and consequently reduce the environmental pollution.